THE DEVELOPMENT OF COMMUNITY ENTERPRISE GROUPS THROUGH CREATIVE LOCAL WISDOM TO SOLVE POVERTY ISSUES AND REDUCE ECONOMIC INEQUALITY AMONG COMMUNITY ENTERPRISE GROUPS IN MAE HONG SON PROVINCE - Piyanonthasin, Weerawit (Journal of MCU Nakhondhat, 2026)
The purposes of this research were 1) study the problems and conditions in developing community enterprise groups through creative local wisdom, 2) study the creative economic wisdom of community enterprise groups, and 3) study approaches to enhance the potential of community enterprise groups. This is a mixed-method research employing both qualitative and quantitative research approaches. The sample groups consisted of 245 members of community enterprise entrepreneurial groups, 25 model community enterprise groups, and 5 business experts. Questionnaires and data recording forms were used as data collection instruments. Statistical methods used included frequency, percentage, mean, standard deviation, and content analysis for the qualitative research. The research findings revealed that problems and obstacles in all components were at a high level as follows, management ( =3.83, =0.67), followed by community enterprise leadership ( =3.81, =0.70), production ( =3.73, =0.80), knowledge management ( =3.67, =0.78), participation ( =3.67, =0.77), marketing ( =3.63, =0.76), and finance ( =3.48, =0.76). The study of creative wisdom among community enterprise groups found that conservation-oriented creative wisdom was most utilized ( =3.81, =0.70), followed by application ( =3.74, =0.77), restoration ( =3.71, =0.69), and new creation ( =3.69, =0.78). The business environment analysis revealed, Strength - community enterprise products have distinctive characteristics, Weakness - community enterprises lack innovation to enhance production efficiency, Opportunity - Mae Hong Son Province is recognized by tourists as a cultural tourism destination, and Threat - products derived from local wisdom are not of general interest to consumers. as for approaches to enhance production capacity, local wisdom should be applied and innovation should be adapted in the production process to align with consumer demands.